Analisis Kemampuan Siswa Kelas XI dalam Memahami Materi Pembelajaran Pak di Sekolah SMA Kristen Tobelo - Tomi Itje; Karwanto O Hokakay; Meinggrit Bawohe (Matheteuo: Religious Studies, 2021)
This research aims to (1) determine the ability of class XI students in understanding the concept of Christian religious education material at Tobelo Christian High School, (2) the obstacles of XI class students in understanding the concept of Christian religious education material at Tobelo Christian High School. This type of research is descriptive qualitative with a data triangulation approach. Data were obtained using interviews, observation, questionnaires, and documentation techniques. The data were analyzed through the stages of reduction, data display, verification, and conclusion. The results of the study show that there are 13 aspects of the concept of Christian religious education material categories that can be known, namely; 21.05% or 4 students from 19 respondents in the very good category, 52.63% or 10 students from 19 students who understand the concept of Christian Religious Education material well, 15.78% or 3 students from 19 students who understand the concept of Christian Religious Education material fairly good and 10.52% or 2 students out of 19 students who understand the concept of Christian Religious Education material less well. There are several factors that affect students' ability to understand the concept of Christian religious education material in the implementation of the learning process based on the results of research in the field, namely (1) Students in class XI are lack motivation in learning, (2) learning methods are not appropriate by the teacher, and (3 ) students spend more time playing than studying time; (4) lack of learning communication between teachers and students, (5) lack of understanding of teachers in understanding their duties and roles as learners. Based on the results of the research, it showed that there were real efforts made by teachers and the curriculum and school principals through learning evaluation activities and classroom learning supervision.